KONSEP PEMIKIRAN FILSAFATI MUHAMMAD IQBAL TENTANG PENDIDIKAN DAN RELEVANSINYA DENGAN PEMBANGUNAN KARAKTER BAGI BANGSA INDONESIA - Widyastini, Widyastini (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2017)
The title of this research is the concept of philosophical thought of Muhammad Iqbal about education and its relevance of character development for Indonesian. The objective of this research is to find something new on Muhammad Iqbal’s view about education and its relevance with characters development of Indonesian and to do critical evaluation toward Muhammad Iqbal’s thought about education in his books.The method of this research is library research using books as source of data with data analysis method consisting of: data reduction, data classification, data display and hermeneutics method. Hermeneutics is a method to find meaning with countain description methodical, verstehen, interpretation and heuristics. Description is a method collecting verbal data that is and explanation of philosophical thought. Verstehen is a method to comprehend the object of the research by using logic principles. Interpretation is a method to inform the essence of reality. Heuristics is a method to find new things.The result of this research was education according to Muhammad Iqbal view, it should be directed to revive, to support human individuality and to find the source of national culture with giving benefit than created creative activity. The essence of Muhammad Iqbal’s thought about education with the character development of Indonesian could give inspiration to every Indonesian people in order to do self correction toward education that has been carried out so than realized the right situation of education with the noble values as stated in Pancasila.